COVID-19 Vaccine Selfie: Why Does It Matter?. Issue 6 (2nd November 2021) - Ittefaq, Muhammad; Abwao, Mauryne; Ahmad Kamboh, Shafiq
ABSTRACT: With the ongoing COVID-19 vaccine rollouts, it is a popular trend among vaccine recipients to share their vaccine selfies on their Facebook, Instagram, and Twitter accounts. Individuals sharing their selfies are mostly laypeople, celebrities, political leaders, and healthcare workers. The selfies are either taken during or after the administration of the vaccine and being posted while using specifically created Facebook COVID-19 vaccine profile frames. Health communication experts enumerate several beneficial values attached to vaccine selfie culture, yet there exists some skepticism as well. Today, while having the latest communication technology in our hands, we are better equipped to disseminate useful knowledge about vaccine efficacy, share latest updates about the vaccine rollouts, show others the vaccine related actual data to debunk myths, upload our vaccine selfies to encourage vaccine acceptance, and focus on the social and economic benefits of the vaccines. If anti-vaxxers are excessively using social media to reduce vaccine acceptance rate; in parallel, the public health experts, organizations, and individuals should take advantage of the social media platforms to counter the anti-vaxxers propaganda messages. Finally, a vaccine selfie coupled with positive captions and motivational hashtags would be greatly helpful in reducing vaccine hesitancy among all factions of the society.